Supporting Entrepreneurship through Social Media - Putri, S O; Fathurrahman, A (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to look at the effects of social media feeds that are used to support business. To support the research, the author used a descriptive method by examining several Instagram accounts in the business of photo and video documentation viewed from their Instagram feeds. The results of the study showed that a good, interesting and creative Instagram feed would give its own branding to the Instagram account or business, and it could also attract potential new customers. From these results, the authors found that an interesting and creative Instagram feed would provide branding and had its own character, while also being able to persuade consumers. This was because manufacturing interesting and creative feeds could make consumers more interested in the services we offer. Evidently, this was very influential on the development of the business that we make.